HLA and environmental interactions in sarcoidosis - Rossman, M.D.; Thompson, B.; Frederick, et al., M. (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2008)
Sarcoidosis is a systemic granulomatosis of unknown etiology despite being described over 100 years ago. While both genetic predisposition and environmental exposures have been proposed as playing a role in this disease, there have not been any systematic investigations of gene-environmental interaction in this disease. In the ACCESS dataset, detailed environmental histories and high resolution HLA class II typing were performed on 476 cases of newly diagnosed sarcoidosis and 476 matched controls from the patients’ community. We evaluated gene-environmental interactions in exposures or HLA class II alleles that were present in > 5% of the population and had an odd ratio of > 1.0. Four exposures and four HLA Class II alleles met these criteria and were evaluated. Significant interaction was observed between HLA DRB1*1101 and insecticide exposure at work (p < 0.10) and suggestive interaction was observed between HLA DRB1*1101 and exposure to mold and musty odors and DRB1*1501 and insecticide exposure at work (P < 0.15). In addition, HLA DRB1*1101 and insecticide exposure at work was associated with extrapulmonary sarcoidosis, specifically cardiac sarcoidosis and hypercalcemia (p